Schadenfreude among Indonesian University Students: The Role of Agreeableness, Extraversion, and Demographic Factors - Nashori, Fuad; Ramdani, Zulmi; Khairunnisa, Nadea Zulfa; Wijaya, Taufik Dwi; Azzizah, Syifa Nur (International Journal of Islamic Educational Psychology, 2025)
Some college students are described as experiencing schadenfreude toward their peers. Schadenfreude is caused by personality and demographic factors. This study aims to examine the influence of agreeableness, extraversion, and demographic factors on schadenfreude among Indonesian university students. Data were collected through self-report questionnaires using the Schadenfreude Scale (SS) and the Big Five Personality Inventory (BFI), administered to 207 university students in Yogyakarta, Indonesia. Multiple regression analysis was employed to analyze the data. The results indicated that agreeableness, age, duration of study, and gender significantly influenced students' experiences of schadenfreude, while extraversion did not have a significant effect. Additionally, the findings revealed that male students tended to have higher schadenfreude scores compared to female students. Older students also reported lower levels of schadenfreude than their younger counterparts. The higher the duration of study, the more  schadenfreude  will also increase. These findings provide vital insights for the field of social psychology in an educational context, particularly in developing educational and psychological strategies to understand and manage the dynamics of negative emotions among students, thereby fostering more empathetic and emotionally intelligent learning environments.